Aplikasi Pengenalan Motif Tenunan Kolana Berbasis Web Sebagai Upaya Pelestarian Budaya Menggunakan Metode Iterative - Malaikosa, Erna Juniasti; Loban, Jeni Marianti; Palle, Adrial Orians (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
Kolana weaving includes gebitir keti awitaing, gebitir keti sikaigimit, gebitir keti pupu miyoku, gebitir brand, keng sikay, angrasok and kenglimi maut with types of weaving in the form of sarongs, blankets and shawls and have various motifs. During interviews with weavers, there were still weavers who did not understand the meaning of the motifs behind the weaving used. If this is not preserved, the woven cultural heritage inherited from our ancestors will slowly disappear and become extinct. The aim of this research is to build a web-based application that can provide data and describe the meaning of motifs in pictures of kolana woven fabric in detail and completely. The method used in building this application is an iterative method with development stages in the form of requirements, analysis, design, system, implementation, testing, review, maintenance, which are also modeled using the Unified Modeling Language (UML) modeling technique. The result of this research is the availability of web-based information describing the meaning of motifs from 5 types of kolana woven fabric which can be used as a media for preserving kolana weaving.